Stock return comovement around the Dow Jones Islamic Market World Index revisions - Mazouz, Khelifa; Mohamed, Abdulkadir; Saadouni, Brahim (Elsevier, 2016)
We examine patterns of comovement in stock returns around the Dow Jones Islamic Market World Index (DJIMWI) quarterly revision events. Our analysis is based on a sample of 8250 companies from eighteen countries during the period May 1999–June 2012. We find that a stock’s comovement with the DJIMWI increases when it joins and decreases when it leaves the index. We also find that the comovement of newly added (deleted) stocks with the existing DJIMWI constituents increases (declines) during periods of high trading activity and during the month of Ramadan. Further tests reveal that changes in the fundamentals have no impact on the comovements of added and deleted stocks. Overall, our results indicate that stock returns respond to the emotional state of investors around information-free events.
Keywords: DJIMWI revisions; Religion; Comovement; Ramadan effect; Behavioral finance; Market efficiency